The Impact of Switch Leadership on Project Success: Empirical Evidence from UAE - Muhammad Tahir; Hummayoun Naeem (European Scientific Journal, ESJ, 2017)
This research project documents an empirical analysis of the switch leadership in project management practices in U.A.E. This is an examination study for which 50 projects were studied representing in U.A.E. The main objective of this research is to study the project leadership phenomenon whereas the impact of switch leadership that plays a pivotal role in achieving project success whiles the inclusion of project manager’s experience. Since the U.A.E has a diverse working environment and it is multicultural research study that represents the present day project environment in U.A.E. The results from the analysis of data obtained through questionnaires, which further explores the degree of impact of switch leadership between distinctive leadership styles and project success and also it was discovered that project manager’s experience does not significantly moderates the relationship between switch leadership and project success. At the end the researcher provides suggestive recommendations for switch in leadership styles displaying the impact on project success.